A South African perspective on some critical issues regarding the OECD model tax convention on income and on capital, with special emphasis on its application to trusts - Du Plessis, Izelle (Stellenbosch University, 2014)
Trusts are used for a variety of purposes, both in South Africa and abroad. Like so many other entities, trusts often do not function only in one jurisdiction and may therefore be exposed to international double taxation. South Africa, like most other states, enters into bi-lateral double taxation treaties, to limit the effects of international double taxation. Most of these treaties are based on the OECD Model Tax Convention on Income and on Capital (the OECD MTC). The South African trust is a unique creature. It is not based on the dual ownership concept on which most common law trusts are based, yet, it is not a juristic person either. The question that this research aims to address is how South Africa will interpret and apply certain provisions of the OECD MTC to trusts. Although the South African position is investigated, it is compared to the positions of the United Kingdom, Canada and the Netherlands. The dissertation starts with an analysis of the trust law in each of the relevant states, followed by an overview of the taxation regime governing trusts (and the parties thereto) in each state. The status of double taxation treaties and their interpretation are examined before certain critical provisions of the OECD MTC are analysed to determine how South Africa will apply these provisions to trusts. Hence it is explored whether a trust will be regarded as a person, whether it may be a resident and a beneficial owner for purposes of the OECD MTC. Furthermore, possible solutions for conflicts of attribution in the application of double tax conventions to trusts are investigated. The dissertation concludes that South Africa will regard a trust as a person for purposes of the OECD MTC. Moreover, some types of trusts may be viewed as residents and as beneficial owners for purposes of the OECD MTC. The solution proposed in the OECD’s Partnership Report should be applied to resolve conflicts of attribution involving trusts.
URI: http://hdl.handle.net/10019.1/95878
Keywords: Double taxation; Income tax; International taxation; OECD Model Tax Convention; South Africa; Taxation; Treaties; Trusts and trustees

An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

Cross-border resolution of banking groups: old demons, current progress, future challenges - Pnevmonidis, Ilias (Université de Genève, 2014)
This contribution focuses on the development of bank resolution regimes as a credible antidote to the ‘too big to fail' problem. The main objective of the analysis is to demonstrate the repercussions and challenges resulting from the implementation of bank resolution schemes on a cross-border level. This work is a selective survey of specific legal questions, which remain relatively unaddressed by academic literature and international standard-setting bodies (e.g. bank resolution triggers or safeguards for bank creditors under bank resolution) or still problematic (e.g. resolution planning or cooperation and information exchange between resolution authorities), in particular when applied in a cross-border context. The author aims to shed more light to the complexities of cross-border bank resolution while trying to answer to the fundamental question: have we ended the ‘too big to fail' problem?
Keywords: Bank-failures; Bank-insolvency; Bank-resolution; Financial-crisis; Insolvency; Systemic-risk; Too-big-to-fail

The position of the whistle-blower in South African law - Isparta, Louise Dorothy (University of South Africa, 2014)
The position of the whistle-blower is known to be a precarious one, with the whistle-blower often either regarded as a hero or a reprehensible traitor. Various pieces of legislation have attempted to remedy their precarious position, especially within the employment relationship, and in which the whistle-blower more often than not has the most to lose. The study at hand has the specific objective of comparing the position of the whistle-blower in terms of South African Law, against 16 specific measurables, and in comparison with the position of the whistle-blower in New Zealand, Australia (Victoria) and the United Kingdom. In the main, the protection offered to the whistle-blower within the South African context, is embodied within the Protected Disclosure Act 26 of 2000 (hereinafter referred to as the “PDA”).In examining the protection afforded to the whistle-blower in South Africa, it is concluded that the framework involved extends much further than just the mere provisions in the PDA. However, there are admitted challenges in respect of this framework as discussed, both legislative and non-legislative, especially in respect of duties of disclosures placed on persons in circumstances in which concurrent protection is not afforded to the whistle-blower. With reference to the comparison in respect of the measurement parameters set, it was found that the PIDA (UK) meets the least amount of the measurements set, with the PDA A (Australia, Victoria) meeting the most of the measurements; the PDA NZ is equally balanced in meeting and not meeting the measurements and the PDA meeting less of the measurements than not, but still meeting more than the PIDA. It was found that had it not been for the catch-all provision contained in section 4 (1) (b) of the PDA, the PDA would have ranked last.
Keywords: Disclosure of information; Lanceur d’alerte; Protected Disclosure Act; Protected disclosure; Public Interest Disclosure Act; Whistle blowing; Whistle-blower

Complex ownership structures, banks' capital structure and performance - Zedek, Nadia (Université de Limoges, 2014)
Cette thèse examine l’impact de la structure actionnariale sur la structure du capital et la performance des banques commerciales européennes sur la période 2002-2010. Elle est composée de trois essais empiriques. Le premier chapitre teste l'effet de la divergence entre les droits de contrôle et les droits pécuniaires d'un actionnaire ultime sur l’ajustement du ratio du capital à son niveau optimal et sur l’offre de crédit par les banques. Les résultats montrent qu’en présence de divergence entre les droits de contrôle et les droits pécuniaires, les banques n’émettent pas du capital pour augmenter leur ratio et, au contraire, elles réduisent leur taille en ralentissant leur offre de prêts. Le chapitre 2 teste l’effet de cette divergence sur la rentabilité et le risque bancaires en temps normal et en temps de crise. Les résultats montrent que bien qu'une divergence entre les droits de contrôle et les droits pécuniaires soit associée en temps normal à une rentabilité plus faible et un risque plus élevé elle a, à contrario, amélioré la rentabilité et contribué à la résilience des banques pendant la crise financière de 2007-2008. Le troisième chapitre teste si le réseau des actionnaires auquel la banque est liée au sein d’une chaîne de contrôle affecte la relation entre la diversification et la performance. Les résultats montrent que la présence des investisseurs institutionnels dans les chaînes de contrôle aide les banques à tirer des bénéfices lorsqu’elles diversifient leurs activités.
Keywords: Actionnariat; Banques; Banques européennes; Capital; Capital Structure; European Banking; Ownership; Structure du capital

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Essays in competition policy - Khimich, Aleksandra (Université Toulouse 1 Capitole, 2014)
Dommage économique causé par les cartels: une évaluation pour les pays en voie de développement (En collaboration avec Marc IVALDI, L'École d'économie de Toulouse et CEPR et Frédéric JENNY, ESSEC Business School, Paris) : La détection et la sanction des cartels reste toujours d'une grande importance pour les autorités de la concurrence développées en raison d'une compréhension claire de leur danger potentiel, et donc des avantages de leur dissuasion. Néanmoins, les pays en développement ont souvent du mal à créer ou à renforcer leur autorité de la concurrence - l'exécution d'une division antitrust est coûteuse et la preuve à l'appui concernant les avantages potentiels est toujours manquante. Présente étude fournit la preuve quantitative manquante. Elle propose une évaluation du dommage économique total causé par les cartels en termes de chiffre d'affaires affecté par les pratiques collusoires ainsi qu'en termes de profits excessifs des ententes découlant de surcharge des consommateurs. Les résultats suggèrent que le préjudice économique totale estimé en termes de profits excessifs divisés par le PIB correspondant peut atteindre jusqu’à 1%. En outre, comme la probabilité annuelle maximale de découvrir une entente déjà existante est estimée à environ 24%, il est suggéré que le dommage économique réel dépasse nos estimations, au moins quatre fois. / Évaluation de la précision des outils proposés dans les lignes directrices sur les fusions (En collaboration avec Marc Ivaldi, L'École d'économie de Toulouse et CEPR et Jérôme Foncel, EQUIPPE, Université de Lille) : Présente étude propose une évaluation complète de la précision de deux outils proposés par les lignes directrices sur les fusions les plus avancés - le critère traditionnel HHI et un plus récent UPP - et défini les conditions économiques qui favorisent les prédictions trompeuses. Les simulations de Monte-Carlo sont utilisées pour créer des économies qui sont utilisés pour mesurer les effets des fusions et d'évaluer la performance des outils d'évaluation choisis. Les résultats suggèrent que le test HHI à une capacité très faible de déterminer le potentiel de l'augmentation des prix lorsqu'il est appliqué à un marché de produits différenciés. Dans son tour, le test UPP peut aussi être très trompeur, même si l'on a une information parfaite sur les principaux ingrédients nécessaires pour le calculer. L’étude démontre que certains d'erreurs de type I et de type II se produit parce que les tests de type UPP par construction ne tiennent pas compte de la ‘pression’ sur le prix subie par le partenaire de fusion. Elle aussi explique comment ce dernier peut être réglé en tenant compte du degré de transmission croisé correspondant. / Le rôle du degré de transmission croisé dans les évaluations des fusions : Présente étude démontre que l'ignorance de l’effet de transmission croisé, et en particulier de son signe, peut conduire à des conclusions erronées dans presque toutes les étapes d’évaluation d’une fusion, y compris la procédure de définition du marché et l'évaluation des effets coordonnés et unilatéraux. Par conséquent, l’étude aussi offre un examen des propriétés de l'ensemble de la matrice des degrés de transmission dans un cadre suffisamment général et en même temps plus pratique pour les concentrations horizontales et tire les caractéristiques exactes des systèmes d'offre et de demande qui affectent le signe du degré de transmission croisé.
Keywords: Cartels; Competencia; Competition law; Concurrence; Conditions économiques; Droit international; Pays en voie de développement; Politique de la concurrence

The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Accepted: 2014-10-01T07:01:54Z
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

Arbitration in administrative contracts : comparative law perspective - Lin, Ching-Lang (Institut d'études politiques, 2014)
Il a été longuement discuté de savoir si le système d'arbitrage est applicable pour régler les litiges administratifs qui concernent certains contrats administratifs ou d’autres sans rapport avec le contrat administratif. Dans cette thèse, les trois questions spécifiques sont analysées tour à tour : (1) Est-il possible pour un arbitre ou un tribunal arbitral de trancher des questions relevant du droit administratif? (2) Y a-t-il, ou devrait-il y avoir, des limitations à l'autorité des arbitres et des tribunaux arbitraux? (3) Enfin, après la délivrance d'une sentence arbitrale, quel rôle devrait jouer l'État dans la phase de contrôle judiciaire? La première question concerne l'arbitrabilité et a été discutée dans la première partie (FIRST PART: ARBITRABILITY). La deuxième question a été discutée dans la deuxième partie (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Enfin, sur la dernière question a fait l’objet d’une troisième partie (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). Dans cette thèse, nous avons comparé les systèmes de quatre pays (Canada, Chine, France, Taïwan). En conclusion, nous pouvons donc conclure que l’évolution de la conception du contrat administratif implique de nombreux aspects, y compris les aspects juridiques, économiques, politiques et même culturels. Le développement de la fonction de contentieux administratif, comme ‘’subjectivement orienté" ou "objectivement orienté" aura une incidence sur l'acceptation de l'arbitrage en matière administrative. Dans l'ensemble, l'arbitrage sera plus acceptable dans les systèmes dont la fonction est plus ‘’subjectivement orientée" que dans ceux dont la fonction est "objectivement orientée". While arbitration has traditionally been considered as a means to resolve private disputes, its role in disputes involving administrative contracts is a crucial question in administrative law. In brief, the three specific questions are (1) Can arbitrators or arbitral tribunals decide issues involving administrative law? and (2) Is there, or should there be, any limitation on the authority of arbitrators or arbitral tribunals? (3) Moreover, after the issue of an arbitration award, what role should the State play in the judicial review phase? The first question, the issue of arbitrability, is discussed in part 1 (FIRST PART: ARBITRABILITY). The second question will be discussed in part 2 (SECOND PART: PARTICULAR QUESTIONS OF ADMINISTRATIVE MATTERS IN ARBITRATION PROCEDURE). Finally, on the question of what happens after the arbitration award, we will discuss judicial review in part 3 (THIRD PART: JUDICIAL REVIEW AND EXECUTION OF ARBITRATION AWARD). We compare legal systems between the four countries: in France, in Canada, in China and in Taiwan. We believe that an administrative contract, at least in its function and conception, is gradually becoming different from a private contract. Innovation with respect to administrative contracts will also reflect the concentration and function of the administrative litigation systems in each country. In addition, the “objective” or “subjective” function of administrative litigation will also affect the degree of arbitrability, as well as arbitration procedures. Taken together, arbitration will be more acceptable in systems whose function is more “subjectively oriented” than in those whose function is “objectively oriented". Finally, “the arbitration of administrative matters” traditionally has been an important question in administrative and arbitration law. In the future, we will continue to see it shine in the doctrine and jurisprudence of both the administrative and arbitration law fields.
Keywords: Administrative litigation system; Arbitrability; Arbitrabilité; Arbitrage; Arbitragem; Arbitration; Arbitration award; Contentieux administratif; Contrats administratifs (exécution); Judicial review; Litige; Légalité objective; Objective and subjective function; Prerogative of administrations in contracts; Sentence arbitrale (contestation); Études comparatives

Employees Contract of Employment and Wrongful Dismissal From Service - Ugbele, Sunday; Utobo, O. J. (African Journal of Politics and Administrative Studies, 2014)
Contract of employment was long acknowledged as a subject of genuine and voluntary agreement whose construction or determination should be founded on due notice of the parties thereto. Action for wrongful dismissal would lie if an employment was disturbed, interfered or meddled with, in defiance of the rights of the parties under the contract. The objective of this study was, among others, to determine what constituted a valid contract of employment and remedies for wrongful dismissal. The qualitative and documentary method of data collection was adopted by reference to relevant literature and statutory authorities. From the data gathered, and content analyzed, we found that no law could foreclose an employment from determination, nor could an irregular or wrongful dismissal stand. It was recommended, inter alia, that beside the need to repeal the Public Officers (Protection) Act, both the employer and employee should, in their official dealings, respect the sanctity of their contract, and permit reasonable future modifications thereto as could lawfully enhance the life of the contract and their legitimate desires.

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

Human capital disclosure in corporate annual reports - Adelowotan, Michael Olajide (University of South Africa, 2014)
It is generally acknowledged that human capital intangibles are major value drivers in the new economy characterised by information and technology. The main purpose of this study is to examine the extent to which companies listed on the Johannesburg Stock Exchange disclose information on human capital related issues. The study combined both qualitative (literature reviews and content analysis) and quantitative (survey questionnaire) methods to collect data of 60 corporate annual reports (CARs) of listed companies in South Africa from survey questionnaires administered on various categories of preparers and users of these CARs. The study made use of 91 human capital disclosure checklists developed from literature reviews for the purpose of data collection. The data analysis was done with the aid of Atlasti-a qualitative data analysis software and SPSS- a quantitative data analysis software. The findings show that majority of the items on the disclosure checklist are not yet disclosed in the CARs even though most of the items on the checklist are adjudged to be useful for organisational value creation. In view of the initial findings of this study, a human capital disclosure framework is recommended.
Keywords: Annual report; Corporation reports; Discretionary disclosures; Human capital; Human capital disclosure framework; Intangible assets; Intangible property; Intellectual capital; Mandatory disclosures; Personnel management

Substantive equality, affirmative action and the alleviation of poverty in South Africa : a socio-legal inquiry - Katiyatiya, Luyando Martha (Stellenbosch University, 2014)
Substantive equality is a constitutional imperative, hence the need for strategies that attempt to realise it for the sake of genuine social reconstruction. The principle of equality runs through all other rights in the South African Constitution. Be that as it may, equality is an elusive concept, which makes its achievement an ambitious task. Nonetheless, there are strategies that attempt to bring to the fore the ‘substance’ of the concept in order to ensure the actual realisation of socio-economic benefits. Such strategies include, among others: social security, education, economic empowerment, skills development and affirmative action. This study will focus on the latter of these strategies, namely affirmative action. Although affirmative action is practised around the world, one of the (many) criticisms of the policy is that it fails to bring about substantive or structural change. In other words, it may change the racial and gender composition of the classroom or the workplace, but does not address the challenges that cause the disadvantages of marginalised groups in the first place. It is arguable that affirmative action has increased inequality in South Africa by benefiting the apex of the class structure and not the majority of the population living in abject poverty. This study develops a theoretical analysis of the link between status (race, sex and ethnicity) and socio-economic disadvantage, and the central question that the study addresses is the following: How can the policy of affirmative action be redesigned to ensure that it benefits the socio-economically disadvantaged? A secondary question that is investigated is whether affirmative action can contribute to the development of human capacities in the context of poverty alleviation. It is arguable that substantive equality facilitates the adoption of strategies (such as affirmative action) to address socio-economic inequality, poverty and social exclusion. The research suggests that a paradigm shift is necessary in order to reconceive of affirmative action as a policy that does not only focus on ensuring ‘equitable representation’ of disadvantaged groups in the workforce or the classroom, but also provides for the development of human capacities. This can be achieved if one adopts an expansive view of affirmative action and if one utilises class as one of the numerous criteria for determining the beneficiaries of the policy.
URI: http://hdl.handle.net/10019.1/86607
Keywords: Affirmative action programs; Equality before the law; Politics and government; Public welfare; Social conditions; South Africa

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Modernizing and harmonizing international contract law: the CISG and the Unidroit Principles continue to provide the best way forward - Dennis, Michael J. (Uniform Law Review, 2014)

International sales contracts in Congolese law : a comparative analysis - Kahindo, Nguru Aristide (University of South Africa, 2014)
To regulate and facilitate are the main functions of legal rules. These purposes are achieved by a harmonised legal system by which the law becomes identical in numerous jurisdictions. The process to unify the law of sale internationally started in the 1920s and culminated, in 1988, in the implementation of the CISG. This Convention intends to provide clarity for most international sales transactions by regulating the formation of contracts, and the rights and obligations of the seller and the buyer resulting from the contract. The CISG has these days enjoyed much ratification and influenced a number of legislation reforms worldwide. Despite the role it played during the drafting process of the CISG, the DRC has not yet ratified it. Instead, the country continued to rely, until recently, on colonial legislations which had become out-dated, and inadequate to meet modern international sales contracts requirements. The situation appears to have been improved a year ago as the effect of the adoption of OHADA law whose Commercial Act is largely inspired by the CISG. Because the introduction of OHADA law in the DRC is very recent, this study intends to assess the current state of Congolese sales law by comparing it with the CISG and South African law, which is non-CISG but modernised. The comparative study aims at establishing whether current Congolese law, as amended by OHADA law, is sufficient or has shortcomings; if it has some, it aims to identify those shortcomings, and make suggestions for their improvements. After discussion, it has been discovered that the ratification of OHADA law has significantly improved Congolese domestic sales law. Given that there remain certain unresolved shortcomings in Congolese international sales law, however, the study ends by a proposal for the accession of the DRC to the CISG in order to fill them.
Keywords: Congo (Democratic Republic); Congolese contract law; Congolese sales law; Contracts; Export sales contracts; Formation of the contract; International sales law; OHADA law; Obligations of the buyer; Obligations of the seller; Sale of goods; South Africa; South African contract law; South African sales law

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

An evaluation of the predictive value of bank fair values - Ehalaiye, Oludimu Oluseun (Victoria University of Wellington, 2014)
This thesis examines whether the net asset fair values of banks possess predictive ability for the banks’ future cash flows and earnings. This is an important issue considering the arguments for and against the wider use of fair value accounting for banks’ financial instruments and the claim by some that fair values during economic recessions (where markets may be illiquid) are irrelevant and largely unreliable. A number of studies have found that the explanatory power of bank fair values when compared to traditional historical cost are more value-relevant based on capital market reactions. However, there is a very limited literature on how bank fair values are related to the future performance (e.g. earnings and cash flow) of banks. This study fills this gap by providing empirical evidence on the relationship between U.S. bank fair value disclosures and banks’ future performance as measured by operating cash flows and earnings over a three-period future horizon. Furthermore, the thesis provides evidence on the relationship between bank fair values, in terms of the levels classification introduced during the 2008 global financial crisis, and the future performance of banks, thus showing whether market illiquidity affected the underlying relationships. The study examines two distinct periods. The first study period, 1996-2005, was based on annual data of banks with minimum total assets of $US150 million as of year 1996. The second study period from 2008-2010 (this period encompassed the global financial crisis period and also the levels classification of bank fair values according to SFAS 157), was based on quarterly data of banks with minimum total assets of $US150 million as of the first quarter of 2008. The thesis provides strong evidence that there is a predictive relationship between bank fair values and future bank performance. The evidence is strong during the first study period from 1996 to 2005 where the current net asset fair values of on-balance sheet financial instruments of banks were significantly associated with future operating cash flows and operating earnings of such banks over a three-year future time horizon. However, the predictive relationship between net asset bank fair values and operating cash flows is stronger than the predictive relationship between net asset bank fair values and operating earnings. In the second study period, from 2008 until 2010 the empirical results show strong evidence that there is a predictive relationship between level 1 and level 2 bank fair values and future operating cash flows. The findings from the empirical results were that the current quarter’s level 1 and level 2 net asset fair values of banks were significantly associated with the future quarters’ operating cash flows of such banks. The level 3 net asset fair values of such banks in most cases were not significantly associated with the banks’ future quarterly operating cash flows. The corresponding relationships for operating earnings were that the current quarter’s level 1 net asset fair values of banks were positively associated with the future quarters’ operating earnings of such banks. However, the level 2 net asset fair values of banks were negatively associated with the future quarters’ earnings of such banks. This result is in contrast to the results obtained when the predictive relationship between level 2 bank fair values and future operating cash flows was evaluated, where it is found that both level 1 and level 2 net asset bank fair values are positively related to future quarterly bank cash flows. Further empirical analysis showed that a possible reason behind this disparity was that there was a structural change in the relationship between bank operating cash flows and operating earnings over the course of the first and second study periods, where, in particular, for the second study period (which includes the period of the global financial crisis) there was a systematic downward bias in operating earnings relative to the operating cash flows of the sampled banks. This in turn makes operating earnings a poor proxy for operating cash flows during the second study period. The findings from this study provide confirmation that net asset fair values have predictive ability as argued by Ball (2008); Barth (2006b) and Tweedie (2008). The study findings that net asset fair values have predictive ability is consistent with the FASB’s view that the asset values shown in firm financial statements should communicate information about the potential future financial performance of the affected firms (FASB 2010:17). Furthermore, the study also confirms that objectively determined bank fair values based on market prices rather than model based bank fair values provide greater predictive value in relation to future performance as measured by operating cash flows. Lastly, this thesis showed that during the first study period (where there was no financial crisis) that bank size, capital adequacy and growth prospects, had little impact on the results obtained, while for the second study period, there were cases where bank size and bank capital ratios did have a significant impact on the predictive relationship between bank fair values and future cash flows. The study contributes to the fair value accounting and accounting standard-setting literature and highlights that fair values have predictive ability, especially with respect to future operating cash flows of banks, both during and outside of periods of financial crisis.
Keywords: Economic forecasting; Fair value; Predictive value

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Alternative Dispute Resolution (ADR): An Overview of Some Common Mechanisms, and their Strengths and Weaknesses in Context - Perrin, Harry (The Plymouth Law & Criminal Justice Review, 2014)
Alternative Dispute Resolution, or ’ADR’, offers parties in dispute an alternative to traditional court-based litigation, which is often seen as slow, costly and ineffective. ADR frequently involves a neutral third party who will settle or facilitate resolution of the dispute. This paper examines three common ADR mechanisms, adjudication, arbitration and mediation, and explores their relative advantages and disadvantages in different contexts.
Keywords: ADR; Adjudication; Alternative dispute resolution; Arbitration; Construction adjudication; Mediation; Negotiation

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

A macro-financial theory of corporate financing and forecast modelling of market movements - Sutton, David (Victoria University of Wellington, 2014)
This thesis identifies a gap in existing theories of corporate finance. This gap is an implication of a Keynesian-Minskian analysis of markets and market-based economies. From a founding theoretical perspective rooted in the view that markets are not reliably efficient the case is developed that past price trend extrapolation is an important factor in corporate financing decisions. At a macro-financial level, companies repurchase equity over periods of strong market rises, while increasing debt at the same time. During periods of sustained, substantial market decline debt is retired and large new equity issues occur. This change in corporate financing is implicitly expensive as relatively low prices are realised for the new stock issued at these times. These factors suggest that conventional theories of corporate financing decisions that rely on corporate rationality and optimisation do not provide a compelling fit with observations in the period 1980-2012. Moreover, inference to Minsky’s (1986) argument that companies are compelled through market declines to shore up their balance sheets provides a better fit with the evidence. These arguments form the basis for the development of the ‘extrapolative expectations’ theory of corporate finance. The second major development in this thesis draws on the theoretical development outlined above to create market movement description and prediction models. These models operate on data drawn from the US Standard & Poors 500 index over the period 1980-2012. Two primary models are developed using binomial logistic regressions. The dichotomous dependent variables are drawn as quarters of market rise (1) or no rise (0), and market falls (1) or no fall (0), respectively for the ‘buy’ model and the ‘sell’ model. Variables tested and those found to add to an explanation of the dependent variables include: corporate debt flows, corporate equity flows, corporate dividend flows, interest rates, market volumes, and historical market levels. Each variable is tested for up to ten lags (two-and-a-half years). Collectively, the variables add to our understanding of those factors influencing (or at the least, signalling) market levels, enabling quarter ahead market forecasts to be made with greater accuracy than arises from an assumption of a random walk. This conclusion crystallises the view that company macro-financial flows and prices are an important cause or signal of future market direction.
Keywords: Corporate financing; Financial Accounting; International Accounting; Macro-financial; Minsky

Dispute resolution in transnational securities transactions - Andreotti E Silva, Tiago (European University Institute, 2014)
This PhD thesis explores how the legal infrastructure for dispute resolution in transnational securities transactions can be improved, considering the regulatory and legal limits of the financial sector in each jurisdiction under study (US, Europe and Brazil). The two main objectives of the work are to a) identify the problems that currently exist for a dispute resolution mechanism in the securities area that can be used transnationally and b) propose solutions that can create a safe legal environment that can be used by the investor in case regulatory rules or the terms of the transaction are breached. The work is justified by the fact that financial markets are legal constructions, making legal certainty and the mechanisms available to enforce the terms of a transaction and apply regulatory rules, especially to the investor that is part of the transaction, essential for the own existence of financial markets. Therefore, the existence of transnational financial markets also depends on the existence of a transnational legal infrastructure, at least broad enough to protect the interest of investors. The argument developed through the work is that the creation of a transnational legal infrastructure depends on the type of dispute that is considered, since not only each type of dispute has its own peculiarities, but the national dispute resolution systems are also built based on the type of dispute that will be submitted to it. To create transnational dispute resolution systems for securities transactions, I propose the use of collective mechanisms of dispute resolution based on the initiative of private parties, the use of arbitration and the establishment of cooperation networks among national alternative dispute resolution mechanisms used to solve financial disputes.
Accepted: 2015-01-15T16:55:51Z
Keywords: Dispute resolution (Law); Financial market; International finance; Security (Law)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Regulating trade in petroleum under the WTO Regime: trade rules vs. reality of the petroleum industry - Bitenov, Gani (McGill University, 2014)
This thesis critically assesses the effectiveness of WTO legal rules in the regulation of international trade in petroleum and highlights potential conflicts between competing resources of energy from the WTO regime’s perspective. The theoretical framework of the thesis is built on the concepts used in natural resource economics, trade theories and international relations. On the basis of Hotelling’s rule of natural resource economics, it proposes a model that reconciles the use of petroleum and the development of renewable sources of energy in the power generation sector, which prospectively can be adopted with respect to the transport sector and other sectors involving energy use. The proposed model may improve global sustainable development. However, it is argued that WTO rules are not properly designed to regulate trade in petroleum and, if applied without due respect to specific issues pertaining to the petroleum industry, would obstruct the achievement of the social optimum, and detrimentally affect the national economies of WTO members and global welfare in general. To improve the WTO system, I propose a reformation of its normative ideology through the introduction of the strategic trade policy theory in complement to the neoclassical theory of trade, at least when trade in energy is concerned. On the basis of the study of the applicability of WTO rules to trade in petroleum and a review of proposals put forward by other scholars to improve the regulation of trade in energy, it is argued that the most effective way to improve the trading regime is to negotiate a new general agreement on trade in energy.The role of the WTO in the regulation of trade in energy is analyzed through a regime management theory borrowed from international relations studies. It is argued that the WTO as a regime manager is capable of improving the regime by properly maintaining the existing equilibrium and by initiating, and leading in negotiations of a new equilibrium.
https://escholarship.mcgill.ca/concern/theses/ws859j68h
Keywords: Petroleum industry and trade; Trade regulation; WTO trade rules

Three Essays on Financial Distress and Corporate Bankruptcy - Chen, Donghui (McMaster University, 2014)
This thesis explores three important issues in financial distress and corporate bankruptcy: bankruptcy venue choice and creditor recovery, the efficiency of Chapter 11 corporate bankruptcy and distressed exchanges, and the bankruptcy ripple effect on peer firms’ investment policy.
Keywords: Bankruptcy; Contagion effect; Corporate Bankruptcy; Distress exchange; Efficiency; Financial distress; Forum shopping; Insolvency

Three theories of Lex Mercatoria - Cuniberti, Gilles (Columbia Journal of Transnational Law, 2014)

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments

The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Accepted: 2015-02-09T12:46:29Z
Keywords: Consumer protection; Contracts; European Union countries

Establishing an international registration system for the assignment and security interest of receivables - Jon, Woo-Jung (Oxford University, 2014)
Legal systems around the world vary widely in how they deal with the assignment of receivables. This legal variety makes it difficult for financiers to conduct their international receivables financing business. This thesis suggests an International Registration System for the Assignment and Security Interest of Receivables (‘IRSAR’) and proposes a model international convention for the IRSAR (‘proposed IRSAR Convention’), which could help financiers to overcome the obstacles they currently encounter. Under the proposed IRSAR Convention, the international assignment of receivables would be regulated by a unified legal system with respect to priority and perfection. The IRSAR would facilitate international project financing. Furthermore, the IRSAR would enable companies to raise finance from greater ranges of investors around the world through international receivables financing and to dispose of non-performing loans more easily. The proposed IRSAR Convention would succeed the UN Convention on the Assignment of Receivables in International Trade in the attempt of establishing a registration system for international assignments of receivables. The proposed IRSAR Convention confines its scope of application by defining the assignor (or the security provider), inventing the concept of ‘Vehicle for the International Registration System’ (‘VIRS’). The proposed IRSAR Convention applies where the assignor or security provider is a VIRS. An assignment of a receivable where the assignor is a VIRS and a security interest in a receivable where the security provider is a VIRS could be registered in the IRSAR. Under the proposed IRSAR Convention, priority of assignments of and security interests in receivables is determined by the order of registration in the IRSAR. The proposed IRSAR Convention would be a receivables version of the Cape Town Convention. With respect to the contents and effect of registration, it would prescribe a notice-filing system along the lines of that adopted in the UCC Article 9. With respect to the operation of the registration, it would adopt an automatic online registration system operating 24 hours a day, 365 days a year like the International Registry under the Cape Town Convention.
Keywords: Comparative law; Contract; Property law; Restitution; Tort

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

Chapter 4 offer regulation under the 2008 Companies Act - Labuschagne, Frederik J. (University of Pretoria, 2014)
Chapter 4 of the Companies Act of 2008 aims to regulate offers to the public of securities and is reviewed against the principles which underscore the regulation of offerings. An overview of the historical development of the company which is parallel to the regulation of securities shows the crystallized principles which are compared against the development and enactment of the current regulatory regime. The concept of “complete law” as key element to effective regulation is discussed and applied in the review of Chapter 4 determining the effectiveness of the dispensation. The three determining concepts of regulation: the “offer,” “securities” and “public” are studied against the definitions which determine regulation and the inclusion of secondary market regulation of unlisted securities. Serious shortcomings in the process are identified. These errors, together with the practical problems of defining and regulating the secondary market in Chapter 4 read with the remainder of the delineating definitions, concludes that the current system is not in line with the principles of regulation and the Grundnorm of fraud prevention, resulting in Chapter 4 falling under the concept of “incomplete law” resulting in a high probability of enforcement failure and inefficiency. A comparative overview related to the jurisdictions of the United Kingdom and the United States follows with recommendations aimed at amending Chapter 4 relating to the regulatory regime in toto as well as the regulation of unlisted securities in the secondary market.
URI: https://repository.up.ac.za/handle/2263/45981
Keywords: Companies Act; Offer regulation

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Brunel University Research Archive
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Accepted: 2015-02-09T14:17:54Z
Keywords: Consumer protection; European Union countries; Injunctions

The role of competitors in the enforcement of state aid law - Pastor Merchante, Fernando (European University Institute, 2014)
State aid law is made up of rules and procedures whose main characters are the Member States – as the addressees of the norms – and the Commission – as their enforcer. The prominent position of these two actors often overshadows the impact that the administration of the rules on State aid has on private undertakings, be it the beneficiaries of State aids or their competitors. This thesis is concerned with the latter. The aim of the thesis is to assess the extent to which competitors may rely on the rules on State aid to protect themselves against the potentially harmful effects of subsidies and other forms of state, financial assistance to firms. This endeavour raises two challenges. The first challenge is to identify the channels through which competitors may voice their interest in the context of a system of governance to which they are in principle alien. This is the issue of access. The second challenge is assess the likelihood that the Commission shall heed to the concerns voiced by competitors. In other words, the challenge is to gauge the power of influence that competitors may exert through each of these channels. This is the issue of leverage. In order to carry out this inquiry, the thesis scrutinizes the means of redress available to competitors before national courts (“private enforcement”), as well as the opportunities that they have to make their voice heard in the course of the Commission’s procedures (“public enforcement”) – namely, the possibility to lodge complaints, the possibility to participate in the consultation phase of Article 108(2) TFEU and the possibility to seek the judicial review of State aid decisions.
Accepted: 2015-02-09T14:56:15Z
Keywords: Antitrust law; European Union countries; Government aid; Restraint of trade; Subsidies; Unfair Competition

Competition law and standard essential patents : oscillating between protection of patent rights and access to standards - Petrovčič, Urška (European University Institute, 2014)
This thesis explores the way in which EU and U.S. antitrust rules address opportunistic conducts that emerge in the context of standard essential patents (SEPs). The analysis finds that the two systems have very different scopes in addressing those practices: conduct lawful under U.S. antitrust law is condemned by the EU competition law and vice versa. In contrast to other fields of antitrust, the differences between the EU and U.S. approach do not arise from the application of different legal standards, but rather reflect the core divergences in the statutory texts that address unilateral practices. The analysis also shows that both in the European Union and in the United States, competition authorities have tried to increase the scope of competition law—first, by stretching the antitrust doctrines outside established borders, and second, by advocacy measures designed to avoid opportunism related to SEPs. The thesis shows, nonetheless, that both approaches are problematic and a more cautious strategy is needed to avoid the risk of injecting imbalance in the standardization context.
Accepted: 2014-10-02T12:32:07Z
Keywords: Antitrust law; Competencia; Competition law; European Union countries; Patent licenses; Unfair Competition; United States

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry

The requirement of consent for the transfer of shares and freedoms of movement : toward the liberalization of private limited liability companies : a comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law - Vicente, Lécia (European University Institute, 2014)
Toward the Liberalization of Private Limited Companies – A comparative study of the laws of Portugal, France, Italy, Spain, the United Kingdom and the United States and its interplay with EU law’, I try to shed light on the dynamics of private limited liability companies (PLLCs), and how they can be legally designed to become efficient units of economic development in Europe and the United States. I take a social sciences approach to the legal question: How does the design of clauses establishing restrictions on transfer of shares of private limited liability companies affect investment made in these companies and their consequent development? To answer this question, I develop two parallel lines of investigation. First, I undertake an embedded historical study to trace the evolutionary patterns of PLLCs in six countries. Furthermore, I longitudinally track the standards of behavior of market agents in the selected jurisdictions. Second, I develop my legal research by looking at an anomaly regarding the transfer of shares and changes in the ownership structure of these business organizations. Transfer of shares in PLLCs is, for the most part, regulated by default rules which impose restrictions on transfers. Typically, the parties do not contract around these default rules. The anomaly lies in the fact that, even though shareholders of these companies do not opt out of these rules, shareholders often ignore them and/or breach them at a later stage.
Keywords: Business enterprises; Corporate law; Limited liability; Private companies